Pemanfaatan Model-Model Boneka untuk Pengembangan Kemampuan Bahasa Anak Usia Dini - Kustiawan, Usep; Astuti, Wuri; Anisa, Nur (Universitas Negeri Malang, 2023)
Abstract: Early Childhood Teachers in Cluster 9 Sukun District Malang doing their duties do not yet have the knowledge and skills of developing the design and making puppet models as a learning medium in improving the effectiveness and quality of language learning in Early Childhood Education. 9 Sukun Subdistrict, Malang City has knowledge and skills in developing the design and manufacturing of puppet models as a learning medium in improving the effectiveness and quality of language learning in kindergarten. The methods used in the training include: (1) Lectures and Questions and Answers for delivering language skills development materials and techniques for making doll models; (2) Demonstrations to prove the stages of doll making techniques; (3) Giving training assignments in groups to make a package of doll models and simulating the use of doll models in real learning at Early Childhood Education institutions. The results of community service activities are products in the form of production designs and finger puppets and hand puppet models which include: (1) TK PKK BANDULAN: Production Design and Finger Puppet Model Theme about Profession and Production Design and Hand Puppet Model Theme about the Universe; (2) TK AGAPE: Design Production and Model of Finger Puppets Theme about Family and Production Design and Model of Hand Puppet Theme about Plants; (3) TK PLUS KIDS: Production Design and Model of Finger Puppet Themes on Transportation Equipment and Design Production and Model of Hand Puppet Themes on Animals.Abstrak: Guru-guru PAUD di Gugus 9 Kecamatan Sukun Kota Malang dalam menjalankan tugasnya belum memiliki pengetahuan dan keterampilan pengembangan desain dan pembuatan model-model boneka sebagai media pembelajaran dalam meningkatkan efektifitas dan kualitas pembelajaran bahasa di PAUD.Tujuan kegiatan pelatihan diharapkan guru-guru PAUD di Gugus 9 Kecamatan Sukun Kota Malang memiliki pengetahuan dan keterampilan pengembangan desain dan pembuatan model-model boneka sebagai media pembelajaran dalam meningkatkan efektifitas dan kualitas pembelajaran bahasa di TK. Metode yang digunakan dalam pelatihan meliputi: (1) Ceramah dan Tanya jawab untuk menyampaikan materi pengembangan kemampuan berbahasa dan teknik membuat model-model boneka; (2) Demonstrasi untuk memperagakan tahap-tahap teknik pembuatan boneka; (3) Pemberian tugas latihan secara berkelompok untuk membuat satu paket model boneka dan simulasi pemanfaatan model-model boneka dalam pembelajaran yang sesungguhnya di lembaga PAUD. Hasil dari kegiatan pengabdian kepada masyarakat ini yaitu produk berupa desain produksi dan model model boneka jari dan boneka tangan yang meliputi: (1). TK PKK Bandulan: Desain Produksi dan Model Boneka Jari Tema tentang Profesi serta Desain Produksi dan Model Boneka Tangan Tema tentang Alam Semesta; (2). TK AGAPE: Desain Produksi dan Model Boneka Jari Tema tentang Keluarga serta Desain Produksi dan Model Boneka Tangan Tema tentang Tanaman; (3). TK PLUS KIDS: Desain Produksi dan Model Boneka Jari Tema tentang Alat Transportasi serta Desain Produksi dan Model Boneka Tangan Tema tentang Binatang.